Dampak Penggunaan Aplikasi H-Butler Terhadap Efisiensi Standard Operating Procedure Check in dan Check Out di Ayana Resort and Spa Bali - Widayanti, Kadek Sri; Nugraha, I Gede Putra (Jurnal Manajemen Perhotelan dan Pariwisata, 2025)
This research aimed to examine the implementation of the use of the H-butler application at Ayana Resort and Spa Bali which focuses on efficiency and improving check-in and check-out services with an increasingly modern and fast concept. The data collection methods used in this research are interviews, observation, documentation, and literature study. Interviews were conducted with hotel staff and guests. The data was analysed using qualitative methods. This research obtained results where the H-Butler application can reduce Que check-in and check-out, increase operational work efficiency, improve guest communication with staff, and reduce paper usage so as to protect the environment. Thus, the application implemented at Ayana Resort and Spa Bali has succeeded in improving the quality of hotel services and giving a positive image to the hotel.